Interpolation method for spatial distribution of clay content within residual soil - Alfrendo Satyanaga; Aswin Lim; Nurly Gofar (Himpunan Ahli Teknik Tanah Indonesia, 2022)
Residual soil is covering some parts of the tropical country such as Singapore. It is commonly known that residual soil is associated with variability either horizontally or vertically. As a result, it is necessary to have a method to determine the distribution of soil properties to minimize the need to have an excessive amount of boreholes before the commencement of the construction project. This paper presents the suitable interpolation method for the spatial distribution of clay content across Singapore island. The common term related to the spatial distribution of soil properties is called digital soil map. The selection of the best method to generate this map depends on different factors. Therefore, each case requires a thorough evaluation and comparison based on the interpolation results. Singapore's digital elevation model and its boundary were utilized in this study. A digital soil map was developed using ArcGIS software based on two interpolation methods such as ordinary kriging, and the inverse distance weighted method. These two methods were cross-validated and compared based on the regression analysis of the analyses results. Cross-validation was performed to verify the correctness of the mentioned interpolation methods. In order to validate the interpolation results, the mean error and the root mean square error were used. The results suggest that ordinary kriging could be used as a suitable method to generate the spatial distribution of clay content obtained from boreholes in Singapore.